The use of nutritional strategies in the prevention and recovery of injuries in athletes: A literature review (Research, Society and Development, 2024)
Introduction: Musculoskeletal injuries (SCI) represent a serious problem in sports medicine, mainly due to their high prevalence. SCI is a generic term including any trauma involving damage to musculature, bone, tendons, ligaments and other soft tissue. Distension of muscles/tendons and sprains of ligaments result in several negative consequences, in several aspects, such as the development of chronic musculoskeletal pain. Objective: To present nutritional strategies that reduce the risk and improve the treatment and rehabilitation process of musculoskeletal injuries in athletes. Methodology: An integrative literature review was carried out on the use of nutritional strategies in the prevention and recovery of injuries in athletes. Data available in the Virtual Health Library (BVS), Scientific Electronic Library Online (SciELO), Google Scholar and National Library of Medicine (PubMed) bases were used, from the intersection of the descriptors “injuries in athletes”, “nutritional supplementation” , “musculoskeletal pain” and “rehabilitation” to answer the question formulated through the PICO strategy. Results and Discussion: Vitamin-D, collagen supplementation - mainly in association with vitamin-C -, protein, omega-3 and creatine have shown promising results when the intention is to prevent and improve recovery from injuries in athletes. Conclusion: Clinical trials are still limited in this population, so more studies are needed to establish a consensus on doses, serum levels and ideal strategies for athletes.